A Non-Invasive Nomogram for Preoperative Prediction of Microvascular Invasion Risk in Hepatocellular Carcinoma - Wang, Huanhuan; Lu, Ye; Liu, Runkun; Wang, Liang; Liu, Qingguang; Han, Shaoshan (Frontiers in Oncology, 2021)
Background: Microvascular invasion (MVI) is a significant predictive factor for early recurrence, metastasis, and poor prognosis of hepatocellular carcinoma. The aim of the present study is to identify preoperative factors for predicting MVI, in addition to develop and validate non-invasive nomogram for predicting MVI. Methods: 381 patients with resected HCC were enrolled and divided into a training cohort (n=267) and a validation cohort (n=114). Serum VEGF-A level was examined by enzyme-linked immunosorbent assay (ELISA). Risk factors for MVI were assessed based on univariate and multivariate analyses in the training cohort. A nomogram incorporating independent risk predictors was established and validated. Result：The serum VEGF-A levels in the MVI positive group(n=198) and MVI negative group (n=183) were 215.25±105.68pg/ml and 86.52±62.45pg/ml, respectively(P＜0.05). Serum VEGF-A concentration ≥138.30 pg/ml was an independent risk factor of MVI (OR: 33.088; 95%CI: 12.871- 85.057; P<0.001). Higher serum concentrations of AFP and VEGF-A, lower lymphocyte count, peritumoral enhancement, irregular tumor shape, and intratumoral artery were identified as significant predictors for MVI. The nomogram indicated excellent predictive performance with an AUROC of 0.948 (95% CI: 0.923-0.973) and 0.881 (95% CI: 0.820-0.942) in the training and validation cohorts, respectively. The nomogram showed a good model fit and calibration. Conclusions: Higher serum concentrations of AFP and VEGF-A, lower lymphocyte count, peritumoral enhancement, irregular tumor shape, and intratumoral artery are promising markers for MVI prediction in HCC. A reliable non-invasive nomogram which incorporated blood biomarkers and imaging risk factors was established and validated. The nomogram achieved desirable effectiveness in preoperatively predicting MVI in HCC patients.